Status of Agri-tourism in Punjab - Pinky, Samjetsabam; Dhaliwal , R.K. (Indian Journal of Extension Education, 2017)
The present paper analyses the status of agri-tourism in Punjab state, India. The study was undertaken by randomly selecting 15 registered farmers from Punjab Heritage and Tourism Promotion Board. The data was collected by self interviewing the respondents and through mailed questionnaire. Findings of the study showed that 40 per cent of the respondents were gold membership holder followed by diamond and silver. The daily visit as well as the overnight charge varies for each agri-tourism unit. The least charge was of Jyani natural farm near district Ferozpur. During kharif and rabi season the main crop grown were rice and wheat, respectively, while under plantation crops kinnow had the maximum area and all the agri-tourism units had complete source of irrigation facilities. More than half of the respondents were having large size farm house. Virasat Haveli near Amritsar had the maximum number of tourists annually as it was easily accessible by the tourists whereas the Chandigarh Sardar farm near Fatehgarh Sahid had the lowest number of tourists. All the agri-tourism units offered recreational activities followed by productional and processing activities.
Keywords: Agri-tourism Units; Tourists; Charges